The influences of real time information provided on-board rail services - Bachok, Syahriah; Mohamad, Diana (2010)
The paper reports the first part of two simultaneous studies on urban travel patterns in Malaysia. The first refers a completed research that focused on the variation in mode switching behaviors among rail users in a developing city done by the first author. Meanwhile, the second author deals with the prospective of telecommuting and its relations with travel time estimations and travel time application. This work is still in progress. It aims at modeling such behaviors in the event of services delay, an outcome that will be fed into the planning of supplementary feeder services. It is one of the first attempts at explaining the changes in travel decisions resulting from information provision on-board public transport. In this report, a case study was selected to illustrate the differing impacts of various media on travel decisions. Passengers of a commuter-rail-system servicing Klang Valley conurbation in Malaysia were chosen as respondents of a stated preference survey. Paper presented delay information to test the hypothetical scenarios. Three media (a voice recording, a scrolling multi-lines variable message sign and *.*mpeg movies) were provided. Preliminary findings illustrated the effects of varying the medium of information dissemination. When delay information was conveyed in audio and textual versions, mode change decisions for the continuing journeys were found to be inversely related to delay durations. A similar but inconsistent trend was depicted when visual or graphical media were presented. Significant tests of underlying factors including sociodemographics and trip characteristics also showed some degrees of influences on mode switching behaviors.